Analysis on Mimetics and Their Meanings In The Movie “Ip Man” By Edmond Wong - Muhammad Khairul Ramadhan (Universitas Negeri Makassar, 2022)
Abstract. This research uses the Qualitative Descriptive method according to the Narbuko that analyzed by the research data by watching a full movie of Ip Man. This Study aims to find out the main character that related to the history character of this movie, and to find out the Martial Arts that shown in the movie same as in the real world in this movie. This study resulted that there are several speech and also there is some photos that I showed to everyone are proof of the relationship between mimetics and the movie itself.Keywords: Mimetics, Movie, 8 Sequence Theory, Ip Man, Edmond Wong